Aplicação de redes causais como ferramenta no estudo da eutrofização em reservatórios - Valquíria Flávia Lima Viana (2022)
The construction of the reservoirs impacts on several aspects that must be analyzed, such as: the partial interruption of the natural transport of sediments and nutrients downstream, loss of water due to the increase in the volume evaporated by the water surface of the reservoir. In addition to the social losses related to expropriation, there are also those caused to the fauna and flora of the river and its banks. Cyanobacteria blooms are considered a major problem whose frequency has increased significantly in the world, as a result of the eutrophication process of water bodies, due to the input of nitrogenous and phosphate nutrients originating from the release of clandestine effluents and the use of fertilizers. A small part of planktonic species that can produce toxins, often toxic to mammalian animals and humans, can cause toxic cyanobacteria blooms (HABs), configuring a major problem. In addition to the quantitative availability of water quality monitoring data from aquatic environments, it is becoming increasingly important to define the qualitative characteristics of the information to be obtained based on the intended uses. Therefore, the use of environmental indicators can be considered a tool for synthesizing and aggregating data with the importance of establishing the sequence of causes and effects of anthropic actions, in addition to representing the initial condition of a system, also serving to monitor its evolution, for the adoption of measures to promote environmental quality. In this work, statistical analyzes and a study of the use and occupation of the surroundings of three reservoirs were carried out: Emborcação and Nova Ponte (Hydropower plants) and Rio Manso (water supply), for the application of causal networks with the structure pressure-stateresponse (PSR), as a tool to verify the main factors that contribute to eutrophication and to aid in the diagnosis of these environments, order to anticipate the occurrence of cyanobacterial blooms. The results showed that the use and occupation of the surroundings can contribute significantly to the increase in trophic levels in the reservoirs, which over the years have registered eutrophic to hypereutrophic periods. The ANOVA test showed the trophic state index varied significantly (α=5%) between stations at Nova Ponte reservoir’s monitoring stations, which may be correlated with the increase in agrosilvopastoral activities in the surroundings, especially the increase in central pivots, which practically doubled in 20 years. The use of causal networks is a multidisciplinary approach, with few studies in the literature on its application in reservoirs for evaluate eutrophication processes, which makes it a promising tool in studies of water quality in reservoirs. However, it is of paramount importance that the more robust the database, the better the selection of indicators, and it will elucidate, in greater detail, the complex causal relationships. Finally, it was found that the application of causal networks is a very promising methodology that encompasses several social agents, as well as technical and scientific knowledge in favor of sustainable development and improvements in the management of water resources, and even can be used by river basin management committees.